TRAITORS AND THE MEANING OF TREASON IN AUSTRIA-HUNGARY'S GREAT WAR. (8th September 2015) - Cornwall, Mark
ABSTRACT: Treason is a ubiquitous historical phenomenon, one particularly associated with regime instability or wartime loyalties. This paper explores the practice and prosecution of treason in the last decades of the Habsburg monarchy with a special focus on some notorious wartime treason trials. It first sets the rhetoric and law of treason in a comparative historical context before assessing the legal framework supplied by the Austrian penal code of 1852. Although the treason law was exploited quite arbitrarily after 1914, the state authorities in the pre-war decade were already targeting irredentist suspects due to major anxiety about domestic and foreign security. In the Great War, the military were then given extensive powers to prosecute all political crimes including treason, causing a string of show-trials of Bosnian Serbs and some leading Czech politicians. By 1917–18, however, this onslaught on disloyalty was backfiring in the wake of an imperial amnesty: as loyalties shifted away from the Habsburg regime, the former criminals themselves proudly began to assume the title of 'traitor'. The paper is a case-study of how regimes in crisis have used treason as a powerful moral instrument for managing allegiance. It also offers a new basis for understanding instability in the late Habsburg monarchy.